Estudo da influência de um programa centrado na dança de salão sobre o desempenho motor de escolares de 8 a 10 anos de idade - Maia, Maria Aparecida Coimbra (2009)
The purpose of this research is to analyze the influence of ballroom dance beginners level in the school focusing the students motor performance associated to the perception of competence. From the type almost-experimental, it proposes to systemize and to make a ballroom dance teaching-learning program, specially built for this research; to analyze the level of personal efficiency for the ballroom dance skill and to identify the perception of competence levels in the pre and post test; to evaluate the motor coordination levels before and after the application of the beginners level ballroom dance program; to compare the revealed results of the testes between one group enrolled in the ballroom dance program to another group participating in the Physical Education classes as well but not enrolled in ballroom dance program. This program was done with the participation of 89 students from the 3rd grade elementary school of a public school in Maringa-Pr. The measurements instruments used in this research were: the inventory of personal efficiency of Valentini and Toigo (2006) adapted for the ballroom dance; the Perception of Competence Scale of Harter (1985) adapted by Fiorese (1993) and the Kiphard and Schilling.s KTK test (1974), translated by Gorla (1997) for the motor coordination evaluation. The data of this research was analyzed by the descriptive statistic and the á of Croanbach, the Kappa test, the linear model of the mixed effects and correlation coefficient of Pearson, adapting p<00,5. The results of the inventory show that the children had little experience with the ballroom dance, but the majority of them would like to learn it, furthermore they felt more capable of dancing after the intervention. Both groups showed moderate level and high perception of competence, in the subscales: scholar competence, social acceptance, athletic competence, global value, what implied that the children were satisfied with their performance in several skills of their lives. The KTK results indicated significant improvements of the experimental group in the tasks: balance beam, (p<0,001), jumps on one foot, (p<000), side.s jumps (0,001) and transfers on the ramp (p=0,005). The control group showed significant improvement on the bar beam task (p=0,034). When the general motor quotient was in focus, the experimental group indicated a significant improvement (p<0,001) as well the control group (p=0,057). However when the motor quotient in percentage was being analyzed, only the experimental group showed significant difference in the post test (p<0,001). The results also indicated that they have internal correlation in both instruments, although not between them, except between the motor quotient and social acceptance. In conclusion, the beginners level ballroom dance program in the school can contribute significantly for the motor performance demonstrated through the scholar motor coordination enhancement (or the children in the same age group), with effects on the maintenance of the consistence of the perception of the competence after the participation in the program. This allows proposing its effective inclusion in the subject Physical Education scholar.